Pemilihan Waktu Ice Compression Pada Timbulnya Delayed Onset Muscle Soreness Setelah Latihan Submaksimal - Asyiraq, Muhammad Ferdy; Handayani, Selfi; Ghozali, Dhoni Akbar; Munawaroh, Siti (Faculty of Sport and Health Sciences, 2022)
The study aims to determine the timing of ice compression on the onset of DOMS after submaximal exercise. This research is experimental with post-test only control group design. Thirty students of the Faculty of Medicine, Sebelas Maret University participated as subjects. Subjects were divided into three groups, control, treatment 1 hour after exercise, and 4 hours after. Submaximal exercise is done by step test. Ice compression was given for 10 minutes on subject’s front thigh muscles. DOMS pain was assessed using the VAS pain scale. The collected data were analyzed using the one way Anova test and continued with the Post Hoc LSD test. The results of the analysis using the one way Anova test showed a significant difference between the three research groups and the Post Hoc test showed no significant difference between two treatment groups, but the treatment 4 hours group had lower pain scale on VAS. Ice compression after 4 hours exercise can inhibit the macrophages which were the main immune cells for inflammatory reactions. From this study, it was concluded that the most effective timing of ice compression on the onset of DOMS was 4 hours after submaximal exercise.